2021
DOI: 10.1152/jn.00711.2020
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of low and high doses of fentanyl in control and β-arrestin 2-deficient mice

Abstract: We have investigated the potential acute desensitizing role of the beta arrestin 2 (b-arr2) pathway on the ventilatory depression produced by levels of fentanyl ranging from analgesic to life-threatening (0.1 to 60 mg/kg IP) in control and b-arr2 deficient non-sedated mice. Fentanyl at doses of 0.1, 0.5 and 1 mg/kg IP - corresponding to the doses previously used to study the role of b-arr2 arrestin pathway - decreased ventilation, but along the V̇E/V̇CO2 relationship established in baseline conditions, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In stark contrast to the original report (26), each laboratory found that the ability of morphine to depress respiration was the same with or without the presence of β-arrestin 2. Since then, this finding has been confirmed in no fewer than four further studies (29)(30)(31)(32). Indeed, one of those studies (30) found that following high doses of fentanyl, mice lacking β-arrestin 2 were actually more likely to stop breathing and die than were wild-type mice, a result that certainly does not indicate that G protein-biased agonists at the μ-opioid receptor will be safer.…”
Section: More Recent Studies With Genetically Modified Micementioning
confidence: 96%
“…In stark contrast to the original report (26), each laboratory found that the ability of morphine to depress respiration was the same with or without the presence of β-arrestin 2. Since then, this finding has been confirmed in no fewer than four further studies (29)(30)(31)(32). Indeed, one of those studies (30) found that following high doses of fentanyl, mice lacking β-arrestin 2 were actually more likely to stop breathing and die than were wild-type mice, a result that certainly does not indicate that G protein-biased agonists at the μ-opioid receptor will be safer.…”
Section: More Recent Studies With Genetically Modified Micementioning
confidence: 96%
“…Favourable oliceridine safety profile over morphine when considering emesis 96 and respiratory depression 97 was also reported in human. But other studies applying genetic 98 , 99 , pharmacological 72 or mixed 100 , 101 approaches reported severe adverse effects associated with G-protein biased MOR agonists. Thus, it is unclear if no/reduced efficacy for β -arrestin-2 recruitment by WLB-73502 accounts for its improved side effect profile.…”
Section: Discussionmentioning
confidence: 98%
“…The effect on locomotor activity could also account for some of the reduction in irregularity of breathing, however, it is unlikely to account for the dramatic reduction in apnea frequency, which is a hallmark of the breathing disturbances in RTT mice even in reduced preparations (Abdala et al, 2010(Abdala et al, , 2014. The quinpirole-induced reduction in body temperature and locomotor activity also suggests reductions in metabolic rate, which can stabilize breathing (Gautier, 1996;Haouzi et al, 2021). Thus, the stabilization of breathing observed after quinpirole treatment could be secondary to metabolic and locomotor activity changes.…”
Section: Discussionmentioning
confidence: 99%